Diferenças de salário entre cidades médias e regiões metropolitanas do Sul do Brasil - Dutra, Ricardo de Lemos (2012)
This study has examined the main labor income of employed people, in the medium sized cities and metropolitan regions of Brazil s South region, aiming for the identification of how much they are due to the employee characteristics and how much is due to the location in which they are inserted. In order to achieve the objective a brief literature review was taken upon the unbalanced salaries distribution, Chow s structural break test was used, salaries equations were estimated for medium sized cities and metropolitan regions and Oaxaca s decomposition method was used along with Heckman s correction. The database was taken from Pnad 2009 s micro data. Chow test was significant justifying the distinct labor market analysis, in the medium sized cities and metropolitan region, for Parana state as much as for Rio Grande do Sul state. The estimated parameters of Lambda variable concerning the four units were significantly different from zero, what suggests the presence of sample selection bias, so Heckman procedure was applied to produce non-biased estimators. In Parana state, it was verified that dispersion of income was favorable to the metropolitan region once the regional return effect is responsible for 69,76% of that dispersion. In Rio Grande do Sul state, however, the dispersion was favorable to medium sized cities and the attributes effect is responsible for most of the 93,83% income difference of the dispersion. Human capital and segmentation theories were applied upon the case in study, making it evident that the region where the employees are inserted determines their income as much as their personal characteristics. The region has a strong impact in the salary determination, which gets clearer in the case of Rio Grande do Sul state. However, only living in a higher salary region does not ensure the employee the prize, it is necessary that the individuals seek qualification in order to participate in the labor market and receive their remuneration.